(untitled) (Asian Journal of Agriculture, 2024)
Abstract. Balkrishna A, Gautam AK, Sharma N, Arya V, Khelwade V, Arya D. 2024. Effects of organic fertilizers on growth and yield of field crop cowpea. Asian J Agric 8: 32-40. The present study was carried out to evaluate the efficacy of organic fertilizers on the growth and yield parameters of an annual herbaceous legume crop, cowpea (Vigna unguiculata (L.) Walp.). Randomized Complete Block Design (RCBD) with five fertilizer treatments was used in the Factorial experiments, and Farm Yard Manure (FYM) was used as a base fertilizer in the experimental field. Five different organic fertilizers in six treatment combinations as T0 (Control), T1 (Jaivik Prom), T2 (Pori Potash), T3 (Jaivik Khad + Poshak), T4 (Jaivik Poshak), T5 (Jaivik Khad) were evaluated during the present study. The plant parameters like plant height, shoot biomass, leaf area, total chlorophyll, and yield of pods and seeds parameters were investigated. The results revealed that all fertilizer treatments can enhance crop growth from the initial vegetative phase to the late production stage. A positive impact of all fertilizers on growth and yield was observed on plants at all-time points of 30, 60, and 90 days after sowing. The application of Jaivik Poshak in combination with Jaivik Khad proved significant. Their application also enhanced concentrations of total and available nutrients (NPK) in all treatments. The present study provides important information on the organic fertilizers used in agriculture and concludes that these fertilizers can efficiently enhance the growth and yield of crops, including cowpea.